CRYSTAL STRUCTURE OF PROLYL 4-HYDROXYLASE FROM BACILLUS ANTHRACIS - Culpepper, Megen A. (2010)
Prolyl 4-hydroxylases (P4H) catalyze the posttranslational hydroxylation of proline residues and play a role in collagen production, hypoxia response, and cell wall development. P4Hs belong to the Fe(II)/αKG oxygenases and require Fe(II), α-ketoglutarate (αKG), and O(2) for activity. We report the 1.40 Å structure of a P4H from Bacillus anthracis, the causative agent of anthrax, whose immunodominant exosporium protein BclA contains collagen-like repeat sequences. The structure reveals the double stranded β-helix core fold characteristic of Fe(II)/αKG oxygenases. This fold positions Fe-binding and αKG-binding residues in what is expected to be catalytically-competent orientations and is consistent with proline peptide substrate binding at the active site mouth. Comparisons of the anthrax-P4H structure with Cr-P4H-1 structures reveal similarities in a peptide surface groove. However, sequence and structural comparisons suggest differences in conformation of adjacent loops may change the interaction with peptide substrates. These differences may be the basis of substantial disparity between the K(M) values for the Cr-P4H-1 vs. the anthrax and human P4H enzymes. Additionally, while previous structures of P4H enzymes are monomers, Bacillus anthracis P4H forms an α(2) homodimer and suggests residues important for interactions between the α(2) subunits of the α(2)β(2) human collagen P4H. Thus the anthrax-P4H structure provides insight into the structure and function of the α subunit of human-P4H, which may aid in the development of selective inhibitors of the human-P4H enzyme involved in fibrotic disease.